Liquid crystal seed nucleates liquid–solid phase change in ceria nanoparticles. Issue 6 (12th January 2015) - Sayle, Thi X. T.; Sayle, Lewis W. L.; Sayle, Dean C.
Abstract : MD simulation reveals that the crystalline seed spontaneously evolves a liquid rather than a solid. Abstract : Molecular dynamics (MD) simulation was used to explore the liquid–solid (crystal) phase change of a ceria nanoparticle. The simulations reveal that the crystalline seed, which spontaneously evolves and nucleates crystallisation, is a liquid rather than a solid. Evidence supporting this concept includes: (a) only 3% of the total latent heat of solidification had been liberated after 25% of the nanoparticle had (visibly) crystallised. (b) Cerium ions, comprising the (liquid) crystal seed had the same mobility as cerium ions comprising the amorphous regions. (c) Cerium ion mobility only started to reduce (indicative of solidification) after 25% of the nanoparticle had crystallised. (d) Calculated radial distribution functions (RDF) revealed no long-range structure when 25% of the nanoparticle had (visibly) crystallised. We present evidence that the concept of a liquid crystal seed is more general phenomenon rather than applicable only to nanoceria.